Plan de marketing para el Complejo Arqueológico Ingapirca de la provincia Cañar cantón Cañar, Año 2023 - Calero Rochina, Nancy Rocio (2024)
The present research project aims to propose a tourism marketing plan for the Ingapirca Archaeological Complex in Cañar province, Cañar canton, in order to propose marketing strategies to help the promotion and communication of the attraction; the methodology was based on a mixed approach that is a mixture of a qualitative and quantitative approach, qualitative by the bibliographic analysis and interpretation of the characteristics of the study site and quantitative by the collection of statistical data from the surveys applied to know the tourism profile. Techniques and instruments were applied such as interviews, INP cards, surveys, brainstorming and strategic SWOT, by means of which results were obtained such as; the situational diagnosis in 5 economic-productive, physical-spatial, ecologicalterritorial, sociocultural and political-administrative areas, in which 16 cultural elements were identified that make up the internal part of the complex and 5 elements that are part of the external part of the archaeological site. In order to know the tourist profile, a sample was calculated and surveys were applied to determine the characteristics and needs of the demand that visits the attraction. Finally, the proposal for the tourism marketing plan was designed, defining 8 promotional and communications strategies through the strategic SWOT matrix, which serve as a basis to promote tourism and improve the quality of life of the people, as well as the promotion and communication of the tourism services offered by the site.